Penerapan Pendekatan Andragogi untuk Pemberdayaan Perempuan pada Program Pelatihan Komputer SKB Gudo Kabupaten Jombang - denanda rosbida, medelin; Nugroho, Rivo (J+PLUS UNESA, 2026)
Empowering women through non-formal education is an important strategy for increasing their capacity and independence, particularly in mastering information technology. This study aims to describe and analyze the implementation of the andragogical approach in the computer training program at the Gudo Learning Activity Center (SKB) in Jombang Regency, as well as the use of andragogical principles in improving women's empowerment. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. The research subjects included the head of SKB, mentor teachers, computer trainers, and training participants consisting of factory workers, housewives, and women entrepreneurs. The results of the study indicate that the application of the andragogical approach has been carried out contextually in accordance with the characteristics of adult learners. The training was designed based on the participants' needs, life experiences, and practical orientation. The application of andragogical principles has resulted in increased technical skills, self-confidence, and independence of participants. The computer training program at SKB Gudo has been proven to play a role in strengthening women's empowerment both socially and economically.